22 seconds - Patterson, James, 1947-; Paetro, Maxine (2022)
"22 seconds...until Lindsay Boxer loses her badge--or her life. SFPD Sergeant Lindsay Boxer has guns on her mind. There's buzz of a last-ditch shipment of drugs and weapons crossing the Mexican border ahead of new restrictive gun laws. Before Lindsay can act, her top informant tips her to a case that hits disturbingly close to home. Former cops. Professional hits. All with the same warning scrawled on their bodies: You talk, you die. Now it's Lindsay's turn to choose"--
Includes excerpts from upcoming memoir "James Patterson" by James Patterson.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Women's Murder Club (Imaginary organization) -- Fiction; Women detectives -- California -- San Francisco -- Fiction; Female friendship -- Fiction; Drug traffic -- Fiction; San Francisco (Calif.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)